Prospective assessment of the use of the carbonized wood waste of food industry for the production of activated carbon - Kuzmin, Oleg; Shendrik, Tatiana (My University, 2016)
The paper assessed perspectives of carbonated wood waste for the production of activated carbon, so it can be concluded that the introduction of resource-saving and environmental technologies will lead to restored production in the food industry. В роботі оцінена перспективність використання карбонізованих деревних відходів для виробництва активного вугілля, тому можна зробити висновок, що впровадження ресурсозберігаючих та природоохоронних технологій призведуть до відновлюваного виробництва у харчовій промисловості.
Keywords: деревні відходи; wood wastes; активне вугілля; active coal; хімічна активація; chemical activating; кафедра технології ресторанної і аюрведичної продукції